On Loss and Gain: The Translation of Linguistic Simultaneity in This is How You Lose Her, by Junot Díaz - Lorraine Cresci, Karen (TTR)

(untitled) (Association canadienne de traductologie, 2018)
Pulitzer-prize winning author Junot Díaz stages culture clashes in his work by dramatizing the linguistic tension between English and Spanish. This strategy, which he calls “linguistic simultaneity” (code-switching), is central in his fiction because it expresses his Latino identity, and it is artistically and politically significant. Translators who wish to recreate his texts for another readership are forced to rethink what translation is and thus to consider new paradigms, since code-switching defies the traditional conception of translation as the transposition from one closed linguistic system to another. Translations into one of the languages that make up the fictional universe of the source text (in this case, Spanish) are especially challenging. Focusing on the extent to which translators transpose the linguistic simultaneity of Díaz’s source texts, this paper explores the possible reader responses to strategies used to maintain or downplay linguistic tension in the target texts. A comparison of two translations into Spanish of Diaz’s short stories “The Sun, The Moon, The Stars” and “Otravida, Otravez” from This is How You Lose Her (2012) will illustrate how linguistic simultaneity is recreated.